Validation of the Indonesian version of the Islamic Well-being Scale - Priyadi, Suwanda; A’yyun, Aisyah Qurrota; Harsono, Muhammad Hendri Algilbran; Azmi, Kennasty Sausan (INSPIRA: Indonesian Journal of Psychological Research, 2024)
The Islamic Well-Being Scale (IWBS) is an instrument developed to assess well-being specifically in Muslims. However, the instrument was developed for the Muslim population in Turkey. Therefore, this study aims to translate the IWBS into Indonesian and validate it on a sample of Muslims in Indonesia. The translation of the IWBS was carried out by two professional Turkish translators and evaluated by a reconciliation team. The Indonesian version of the IWBS was then tested on 175 adult Muslims (54 males and 119 females, mean age = 25.8 years, age range = 18–73 years). Ordinal confirmatory factor analysis showed that the fit indices of the one-factor measurement model of the IWBS fit the data (SRMR = 0.055; CFI = 0.988; TLI = 0.985). Internal consistency reliability analysis using Cronbach’s alpha, ordinal alpha, Bollen’s omega, Bentler’s omega, and McDonald’s omega formulas showed satisfactory values, 0.919, 0.959, 0.920, 0.920, and 0.934, respectively. The Indonesian version of the IWBS has good psychometric properties and has the potential to be used as an instrument for measuring Islamic well-being. However, the Indonesian version of the IWBS is recommended to be further tested in a larger sample that represents the entire Indonesian Muslim population.